2021
DOI: 10.1038/s42003-021-02289-6
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the probability of death using proteomics

Abstract: Predicting all-cause mortality risk is challenging and requires extensive medical data. Recently, large-scale proteomics datasets have proven useful for predicting health-related outcomes. Here, we use measurements of levels of 4,684 plasma proteins in 22,913 Icelanders to develop all-cause mortality predictors both for short- and long-term risk. The participants were 18-101 years old with a mean follow up of 13.7 (sd. 4.7) years. During the study period, 7,061 participants died. Our proposed predictor outperf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…Comparative analyses in this article include only other DNA methylation measures of aging. Recent reports suggest valuable information about aging and healthspan may also be captured in metabolomic and proteomic datasets ( Deelen et al, 2019 ; Eiriksdottir et al, 2021 ; Jansen et al, 2021 ; Lehallier et al, 2019 ; Tanaka et al, 2020 ). Future studies should compare DunedinPACE to measures derived from these biological levels of analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative analyses in this article include only other DNA methylation measures of aging. Recent reports suggest valuable information about aging and healthspan may also be captured in metabolomic and proteomic datasets ( Deelen et al, 2019 ; Eiriksdottir et al, 2021 ; Jansen et al, 2021 ; Lehallier et al, 2019 ; Tanaka et al, 2020 ). Future studies should compare DunedinPACE to measures derived from these biological levels of analysis.…”
Section: Discussionmentioning
confidence: 99%
“…13 Also, there is an overlap in proteins (KIM1, GDF-15, REN, OPG) between our model and studies that identified proteins for predicting recurrent atherosclerotic cardiovascular disease 14 and predicting all-cause mortality. 15 Overall, these overlaps suggest that these proteins are markers of pathological processes that are shared among many conditions. Interestingly, our study included the immune response panel, which was not included in any of the other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Scores developed through statistical learning stratify where individuals lie on the disease-risk continuum for a population. While proteomic and metabolomics scores have been developed for certain time-to-event outcomes in isolation 9,[16][17][18][19][20] , these predictors are rarely developed and tested at scale. Proteomic predictors have been trained using the SomaScan platform for diabetes and cardiovascular event risk and multiple lifestyle and health indicators 21 .…”
Section: Introductionmentioning
confidence: 99%